Penerapan Central Event Information Untuk Mencetak Sertifikat dan Verifikasi Dengan QR Code Menggunakan Global Extreme Programming - Untung Rahardja; Erick Febriyanto2; Much Alvin Aldiya (Jurnal Informatika Upgris, 2018)
A certificate is a document stating that someone has fulfilled certain requirements and can practice in a field. The certificate verification procedure in universities is still a lot done manually and sometimes does not verify the certificate. This results in many fake certificates. To overcome this problem, a website is created that utilizes the QR Code with the aim of quickly accessing data verification of a certificate. With QR Code scanning technology, paper-based document fraud can be easily carried out without high costs. Therefore, the design of information systems or the creation of web-based applications is a solution to provide convenience to users in the process of data processing, data retrieval to report generation. In making this application the author uses the Agile Software Development model with the Global Extreme Programming process model. While the tools used are UML (Unified Modeling Language) and ERD (Entity Relationship Diagram).